Implementasi Portal Warga Untuk Pencatatan Data Warga Pada Lingkungan RT 004 Warga Desa Tambun - Khasanah, Fata Nidaul; Putri, Alya Priscilla; Ramadhani, Bianca Salikha; Widodo, Dias Satrio Ajie; Hidayatullah, Dimas Alfauzi; Sanjaya, Dimas; Putra, Eka Dharma; Saputra, Erlangga Dwi; Nurhidayat, Fadayen; Erdiansyah, Fadhli Iqbal; Santoso, Fahrul Bagus; Hadi, Fairuz Irfan; Ramadhan, Farhan Arief (Darma Abdi Karya, 2025)
Manual administration in neighborhood communities (Rukun Tetangga/RT) poses a significant obstacle to achieving transparent and efficient governance at the local level. This community service activity aims to develop a web-based community portal and enhance digital literacy among RT administrators through a comprehensive training program. This study employs an Asset-Based Community Development (ABCD) approach that actively involves RT leaders from the design to implementation phase. The portal was developed using the Laravel framework with MySQL database, offering features for News, Billing, Finance, and Inventory management to support more structured RT administration. Direct training was conducted with RT administrators using hands-on practical methods, demonstrating significant improvements in their ability to operate the system. However, this research also identified ongoing challenges, including limited technical support after the KKN program, community resistance to technology, and financial sustainability concerns. Recommendations include: policy advocacy from village authorities, extension of support period to at least 3-6 months, empowerment of local technology champions, comprehensive documentation, and identification of sustainable financial models. This research demonstrates that the success of RT administrative digitalization depends not merely on the quality of technical systems, but on a strong supporting ecosystem and long-term commitment from all stakeholders.